Literature Review: Standardization of Dayak Onion Bulbs (Eleutherine bulbosa (Mill.) and Garlic (Allium Sativum.) - Sepbrilla Ananda Kusriadi (Cleanliness: Journal of Health Sciences and Medical Research, 2026)
Dayak onion (Eleutherine bulbosa (Mill.)) and garlic/shallot skin (Allium cepa L.) are medicinal plants that have long been used traditionally to treat various diseases such as cancer, diabetes, infections, and hypertension. Research related to these two ingredients shows that standardization processes, both specific and non-specific, are very important to ensure the quality and consistency of herbal products. The results of standardization of ethanol extract of Dayak onion bulbs showed low water content and drying loss, and a total flavonoid content of 1.2%. The content of active compounds such as alkaloids, flavonoids, saponins, and quinones has also been identified through phytochemical tests. In shallot skin, the IC₅₀ value against DPPH free radicals reached 152.65 µg/mL with high flavonoid levels (7.84 mg QE/g), while fermented garlic showed very high polyphenol and flavonoid contents (>12% and >2%). The demonstrated pharmacological activities include antioxidant, antidiabetic, anticancer, antimicrobial, and anti-inflammatory properties, supported by the presence of key bioactive compounds. Thus, Dayak onion bulbs and garlic/shallot skins have great potential to be developed as raw materials for safe and effective standardized herbal medicines.